2019
DOI: 10.1111/obr.12919
|View full text |Cite
|
Sign up to set email alerts
|

Patient motivations and expectations prior to bariatric surgery: A qualitative systematic review

Abstract: Bariatric surgery is the most effective treatment for weight loss in individuals with severe and complex obesity. While the extant literature has mostly explored clinical outcomes of surgery, recent research has also examined patients' experiences prior to treatment. This systematic review synthesized findings from qualitative studies investigating patients' motives and expectations prior to undergoing bariatric surgery for weight loss. Twenty-eight studies published in English involving 580 participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 47 publications
(208 reference statements)
8
56
0
1
Order By: Relevance
“…More privileged patients are perhaps more persuasive because they have increased information on alternative treatments as well as striving more for improved quality of life. In a recent systematic review of 28 qualitative studies with 580 participants, many participants believed that weight loss surgery would produce positive psychological impacts by strengthening their personal identities, their relationships and improving their engagement in public and professional life 32. Thus, patients seek an improvement in social life to a large extent.…”
Section: Discussionmentioning
confidence: 99%
“…More privileged patients are perhaps more persuasive because they have increased information on alternative treatments as well as striving more for improved quality of life. In a recent systematic review of 28 qualitative studies with 580 participants, many participants believed that weight loss surgery would produce positive psychological impacts by strengthening their personal identities, their relationships and improving their engagement in public and professional life 32. Thus, patients seek an improvement in social life to a large extent.…”
Section: Discussionmentioning
confidence: 99%
“…Patients interested in undergoing bariatric surgery want to attain 38% weight loss on average and would be disappointed if they did not lose 26% [43], so the modest 5% weight loss typically seen in tier 3 is not likely to affect patients' desire to pursue surgical treatment. In addition, to weight loss, patients expect major psychological and physical improvement after surgery [44]. Hence, it is unlikely that tier 3 services will have a significant impact on reducing the need for bariatric surgery considering the modest weight loss and the lack of evidence regarding major improvement in physical and mental domains.…”
Section: Achieving Weight Loss To Reduce the Number Of People Pursuinmentioning
confidence: 99%
“…The physical and metabolic burdens associated with severe and complex obesity are well-known; however, its psychosocial impact is also of critical importance [ 16 ‱, 17 , 18 ]. These issues may be explored with several methodologies including qualitative methods and assessment of patient-reported outcomes.…”
Section: The Psychosocial Impact Of Severe and Complex Obesitymentioning
confidence: 99%
“…These issues may be explored with several methodologies including qualitative methods and assessment of patient-reported outcomes. A systematic review of qualitative studies of peoples’ motivations for bariatric surgery identified physiological, emotional, cognitive and interpersonal/environmental reasons for wishing to undergo surgery [ 16 ‱]. People with severe and complex obesity suffer from social stigma and discrimination related to their weight which is in turn associated with negative physical and psychological outcomes [ 17 – 22 ].…”
Section: The Psychosocial Impact Of Severe and Complex Obesitymentioning
confidence: 99%